2008
DOI: 10.3174/ajnr.a1405
|View full text |Cite
|
Sign up to set email alerts
|

The Role of MR Imaging in Detecting Nodal Disease in Thyroidectomy Patients with Rising Thyroglobulin Levels

Abstract: BACKGROUND AND PURPOSE:One of the dilemmas facing clinicians treating patients with thyroid cancer is the evaluation of postthyroidectomy patients with rising serum thyroglobulin levels and indeterminate or normal findings on neck sonography. In this study, we examine the role of MR imaging in this subgroup of patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(20 citation statements)
references
References 38 publications
0
20
0
Order By: Relevance
“…Desuter et al [6] reported that only 0.43% (3/696) of thyroid papillary carcinomas had parapharyngeal node metastasis. During the last two decades, looking at only cases with histologically definite diagnosis by surgery, only 39 reported cases were found in the literature (Tables I and II) [6][7][8][9][10][11][12][13][14][15]. Therefore, we reviewed the literature of those 39 cases.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Desuter et al [6] reported that only 0.43% (3/696) of thyroid papillary carcinomas had parapharyngeal node metastasis. During the last two decades, looking at only cases with histologically definite diagnosis by surgery, only 39 reported cases were found in the literature (Tables I and II) [6][7][8][9][10][11][12][13][14][15]. Therefore, we reviewed the literature of those 39 cases.…”
Section: Discussionmentioning
confidence: 97%
“…The presence of node metastasis usually occurs in the internal jugular and recurrent laryngeal chain on the side of the lesion [4,5], so metastasis to the retropharyngeal lymph nodes (RPLN) or parapharyngeal lymph nodes (PPLN) is very rare. Only 39 cases (limited to the cases with histologically definite diagnosis by surgery) have been reported during the last two decades within our literature review (Tables I and II) [6][7][8][9][10][11][12][13][14][15]. Meanwhile, it was reported that there were two lymphatic pathways that connected with a retropharyngeal metastasis from thyroid carcinomas, one is retrograde from jugular chain lymphatics, and the other is direct through the superior thyroid pole by way of the posterior lymphatic trunks, which are reported to be present in 20% of the cases [16].…”
Section: Introductionmentioning
confidence: 99%
“…Other nodal sites that should not be neglected are the lower paratracheal nodes in the superior mediastinum (level VII), and the retropharyngeal (Fig. 6) and retroesophageal groups [ 31 ] . The American Joint Committee on Cancer (AJCC)/Union for International Cancer Control (UICC) TNM staging system classifies nodal stage by site: N1a is level VI nodal disease (including pretracheal, paratracheal, and Delphian nodes), and N1b is involvement of unilateral or bilateral lateral cervical nodes, or superior mediastinal nodes [ 7 ] .…”
Section: Imaging With Ct and Mrimentioning
confidence: 99%
“…MRI also has the ability to detect nodal disease with high protein content from colloid, thyroglobulin, and blood products (Fig. 11) [ 31 ] . If lateral and central neck dissections have been performed, it becomes even more important to carefully evaluate the retropharyngeal nodal groups [ 31 ] .…”
Section: Imaging With Ct and Mrimentioning
confidence: 99%
“…Since the first report in 1970, 1 there have been over 50 published cases in the English-language literature of WDTC metastatic to the retropharyngeal or parapharyngeal lymph nodes. 13 While most of the nodes have been approached transcervically, a small number have been resected transorally. 3,4,[14][15][16] We previously reported the use of transoral ultrasound guidance to safely resect lateral retropharyngeal lymphatic thyroid cancer metastases.…”
mentioning
confidence: 99%